Enhanced performance of denitrifying sulfide removal process at high carbon to nitrogen ratios under micro-aerobic condition. (May 2017) - Chen, Chuan; Zhang, Ruo-Chen; Xu, Xi-Jun; Fang, Ning; Wang, Ai-Jie; Ren, Nan-Qi; Lee, Duu-Jong
Highlights: DSR process at high C/N has enhanced performance at micro-aerobic condition. 80% sulfide is removed with 55% elemental sulfur recovery is reached. Sulfide rebound phenomenon is suppressed under micro-aerobic condition. Enhanced sulfide-oxidizing nitrate-reducing bacteria enhance DSR performance. Abstract: The success of denitrifying sulfide removal (DSR) processes, which simultaneously degrade sulfide, nitrate and organic carbon in the same reactor, counts on synergetic growths of autotrophic and heterotrophic denitrifiers. Feeding wastewaters at high C/N ratio would stimulate overgrowth of heterotrophic bacteria in the DSR reactor so deteriorating the growth of autotrophic denitrifiers. The DSR tests at C/N = 1.26:1, 2:1 or 3:1 and S/N = 5:6 or 5:8 under anaerobic (control) or micro-aerobic conditions were conducted. Anaerobic DSR process has <50% sulfide removal with no elemental sulfur transformation. Under micro-aerobic condition to remove <5% sulfide by chemical oxidation pathway, 100% sulfide removal is achieved by the DSR consortia. Continuous-flow tests under micro-aerobic condition have 70% sulfide removal and 55% elemental sulfur recovery. Trace oxygen enhances activity of sulfide-oxidizing, nitrate-reducing bacteria to accommodate properly the wastewater with high C/N ratios.